Reconfigurable Metasurface for Multifunctional Control of Electromagnetic Waves. Issue 22 (29th September 2017) - Huang, Cheng; Zhang, Changlei; Yang, Jianing; Sun, Bo; Zhao, Bo; Luo, Xiangang
Abstract: Metasurfaces provide a novel strategy to manipulate electromagnetic (EM) waves by controlling the local phase of subwavelength artificial structures within the wavelength scale. So far, many exciting devices have been developed and most of them are based on passive metasurface, which can only perform a specific functionality. It is still very challenging to simultaneously achieve multiple EM functionalities and real‐time reconfigurability in one design. This study reports a reconfigurable metasurface for multifunctional control of EM waves. By controlling tunable elements, the proposed metasurface can dynamically change its local phase distribution to generate predetermined EM responses. Here, the metasurface can generate beam‐splitting performance that can be used to reduce backward scattering waves, and its scattering reduction frequency is tunable. In addition, such metasurface can also achieve dynamical beam deflection and polarization transformation through reconfigurable design of the phase distribution. The above EM functionalities have been experimentally demonstrated at microwave frequencies, which can be switched in real time by a computer‐controlled voltage source. This study paves the way toward the realization of multifunctional metadevices with real‐time and programmable control, showing great potential in applications of smart materials and devices for EM‐wave manipulation. Abstract : A reconfigurable metasurface integrated with multiple electromagnetic (EM) functionalities is proposed. By controlling diode configurations on each metaparticle, such metasurface can change its local phase distribution for generating predetermined EM responses. Experimental results demonstrate that the proposed metasurface can achieve beam splitting, beam deflection, and polarization transformation, and all these EM functionalities can be dynamically switched in real time.